Protoporphyrin IX (PpIX)-conjugated self-lighting nanoparticles for photodynamic therapy: synthesis and characterization - Homayoni, Homa (Henry Stewart Talks, 2015)
Photodynamic therapy (PDT) mechanism of action, PDT & photosensitizer Protoporphyrin IX (PpIX), After Glow NanoParticles (AG NPs), Solving low solubility of PpIX, Conjugation of PpIX to AG NPs, In vitro study: cell viability, cancer cells and UV treatment